Long-term monitoring of tumor-related autophagy in vivo by Fe3O4NO· nanoparticles. (October 2018) - Zhang, Chao; Ren, Jing; He, Jian; Ding, Yin; Huo, Da; Hu, Yong
Abstract: In vivo read-out of autophagy is of great therapeutic and fundamental significance, and yet being conducted exclusively in high cost transgenic animal models. As an attempt to readily monitor the autophagy flux, we herein proposed an autophagy-responsive magnetic resonance imaging based on radical-conjugated magnetic nanoparticles. In principle, both the NO· radical and Fe3 O4 nanoparticles are stable, and separately contributing to an observation of enhanced T 1 -and T 2 -weighted imaging, respectively. Meanwhile, the onset of autophagy concomitantly simulates the mass production of reactive species, and consequently quenches the T 1 -signal of NO·. On this basis, the content of autophagy flux is reflected by the ratio of T 1 -signal intensity to that of T 2 -signal, which is condition-insensitive, as a function of time. Assisted with such strategy, an unprecedented protection role autophagy played in respond to heat stress has been revealed, through which the killing effect of magneto-hyperthermia was greatly impeded. Furthermore, we noticed that the impairment of autophagy through the sequential chemotherapy, can markedly improve the therapeutic outcome, in a manner monitored and thoroughly analyzed using the strategy reported herein. We therefore believe that such a study offers a feasible method for in vivo read-out of autophagy and gives us insights how autophagy influences the therapeutic index of cancer treatments.